CYBER GOVERNANCE STRUGGLE AMONG GREAT POWERS - BAYRAK, Sabri (Cyberpolitik Journal, 2018)
In recent years, studies related to cyber space have increased significantly. This is due to the fact that cyberspace is more involved in life in every sense, and the seriousness and complexity of the number of cyber attacks in the economy, health education and defense systems, and even individuals, is becoming more and more problematic. In the anarchic and unclear cyber area, there are attacks, collaborations, threats and measures against them, just as in the physical world. This situation is affected by states that are an actor of the cyber world. Because they are weaker in this field than other actors, cyber worlds want to be more active and even to dominate. This raises the issue of cyber security. As in the physical environment there is a security issuE in the cyber environment. In order to solve this security issue, cyber governance comes to the fore as a tool. Cyber governance, as a new form of global governance, is to manage the cyber world with more peaceful, human rights-compliant and less secure approaches. Instead of providing governance in the cyber world, states want to dominate and maximize their interests in this area. This raises the problem of cyber governance. Who's going to run? States or other actors? If the States are to govern, which state will it be? What kind of cyber governance do great powers want? This article is basically written to look for answers to these questions.